2002
DOI: 10.1128/mcb.22.4.1253-1265.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Multimerization of Human Telomerase Requires an RNA Interaction Domain in the N Terminus of the Catalytic Subunit

Abstract: Functional human telomerase complexes are minimally composed of the human telomerase RNA (hTR) and a catalytic subunit (human telomerase reverse transcriptase [hTERT]) containing reverse transcriptase (RT)-like motifs. The N terminus of TERT proteins is unique to the telomerase family and has been implicated in catalysis, telomerase RNA binding, and telomerase multimerization, and conserved motifs have been identified by alignment of TERT sequences from multiple organisms. We studied hTERT proteins containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(147 citation statements)
references
References 45 publications
5
140
1
1
Order By: Relevance
“…S8C). Deletion of this motif completely abolishes telomerase activity, whereas RNA binding is only slightly reduced (9). The vertebrate-specific motif VSR contains the third cross-linked residue Phe355 and is part of the CR4/5 binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S8C). Deletion of this motif completely abolishes telomerase activity, whereas RNA binding is only slightly reduced (9). The vertebrate-specific motif VSR contains the third cross-linked residue Phe355 and is part of the CR4/5 binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…The vertebrate TRBD contains an additional vertebrate-specific RNA binding (VSR) motif (9). Substitution and deletion studies found CP, QFP, T, and VSR motifs are required for CR4/5 binding in vertebrates (9,13,14). In budding yeast, the TR contains a conserved three-way junction structure that is similar to the vertebrate CR4/5 domain but does not appear to bind TRBD in vitro (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Being the catalyst interacting with both hTERC and telomeric DNA, hTERT contains four major regions: an N-terminal regulatory (R) domain, RNA-binding (RB) domain, reverse transcription (RT) domain and C-terminal dimerization domain [45]. Several motifs in the R and RB domains of hTERT are conserved in different species, important for various molecular interactions [41,[46][47][48]. As the rate-limiting component of telomerase, hTERT induces immortalization of a number of cell types in culture [49] (reviewed in [50]).…”
Section: Telomeres Telomerase and Cell Immortalizationmentioning
confidence: 99%
“…Human telomerase enzyme functions as a dimer (17)(18)(19). However, the RNA conformation within the telomerase dimer complex is not well studied.…”
Section: In Vivo Confirmation Of the Pseudoknot Structure And Functionmentioning
confidence: 99%